Staphylococci-induced Human Platelet Injury Mediated by Protein A and Immunoglobulin G Fc Fragment Receptor - Hawiger, Jack (1979)
Bloodstream infections with staphylococci are accompanied by thromboembolic complications. We have studied the mechanism of the interaction of staphylococci with human blood platelets. Staphylococci that possess protein A, a bacterial receptor for the Fc fragment of immunoglobulin G (IgG), caused aggregation of human platelets in whole plasma accompanied by release of [(3)H]serotonin. These reactions were time and concentration dependent, requiring two or more staphylococci per platelet to give maximal response within 5 min. The interaction between staphylococci and platelets required the presence of cell wall-bound protein A and of IgG with an intact Fc fragment. It did not require an intact complement system. Cell wall-bound protein A (solid phase) was capable of aggregating human platelets in whole plasma. In contrast, free, solubilized protein A (fluid phase) did not cause measurable aggregation, and release of [(3)H]serotonin was reduced. An excess of free, solubilized protein A blocked aggregation of human platelets induced by staphylococci in whole plasma. The role of the Fc fragment of IgG in the staphylococci-human platelet interaction was demonstrated by an experiment in which free, isolated Fc fragment blocked aggregation of platelets in whole plasma induced by staphylococci. Furthermore, binding of (125)I-protein A to human platelets was demonstrated in the presence of complete IgG with intact Fc fragment but not in the presence of the F(ab)(2) fragment. Binding of the protein A-IgG complex to the human platelet Fc receptor was paralleled by the release of [(3)H]serotonin. These results represent a novel example of the interaction of two phylogenetically different Fc receptors, one on prokaryotic staphylococci and the other on human platelets. Their common ligand, IgG, is amplified by one Fc receptor (protein A) to react with another Fc receptor present on human platelets, which results in membrane-mediated aggregation and release reaction occurring in whole plasma. This mechanism can be of significance in the pathomechanism of thromboembolic complications at the site(s) of intravascular staphylococcal infection.